Rigid conjugated twisted truxene dimers and trimers as electron acceptors - Zhang, Gang; Lami, Vincent; Rominger, Frank; Vaynzof, Yana; Mastalerz, Michael (Angewandte Chemie. International edition, 2016)
A new class of rigid twisted truxenone oligomers with an enlarged π backbone has been established by oxidative dimerization reactions. The resulting extended conjugated systems have large extinction coefficients and low-lying LUMO levels and show good solubility in common organic solvents, thus making them attractive compounds as new electron acceptors in organic electronics. Their suitability as electron acceptors has been demonstrated in bulk-heterojunction organic solar cells with poly(4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl) (PTB7) as the donor material.
Gesehen am 04.10.2021